An Illuminated Psalter of the Quattrocento from the convent of St Francis at Zadar - Kaksic, Nikola (Eikón / Imago, 2016)
The author discusses an illuminated manuscript from the convent of St Francis at Zadar. Nine folios featuring the most representative initials from this manuscript were cut out in 1974 and their whereabouts have been unknown ever since. Only old black and white photographs of this psalter are known in the scholarly literature. With the aid of colour details preserved on a roll flm at the Conservation Office at Zadar, the author attempts to reconstruct their original appearance. He highlights the fact that this psalter has not been thoroughly analyzed or consistently described. He establishes that this is a Liturgical psalter (psalterium feriale) which difers from a Biblical psalter, and that it contains a hymnal (psalterium cum hymnis). Each psalm and hymn begins with an illuminated initial, most of which are decorative. However, the psalter has eight fgural initials (littera historiata), which the author analyzes individually and establishes as a direct refection of the division of the psalter into the days of the liturgical week. Figural decoration was given only to the initials of the first psalm of each new liturgical day (feria), which makes seven in total. Tese are: Psalms I, XXVI, XXXVII, LII, LXVIII, LXXX and XCVII, where Psalm I marks Sunday, Psalm XXVI Monday and so on, until the end of the liturgical week. Figural decoration was also given to the very first initial at the beginning of the psalter which opens with a so-called Invitatorium. Each figural initial is described in detail and special emphasis is given to initial B on folio 5 which represents the richest initial in the entire psalter. At its bottom is a depiction of St Bernardine, rather than St Anthony of Padua or St Francis as has been suggested. In this paper, the author publishes all the initials and places them in the context of their respective psalms. The paper graphically differentiates three types of initials through the use of diferent typesetting. The figural initials, littera historiata, are printed in bold, the italic typeface is applied to the littera dominicalis, while the others, ‘littera ferialis’, which form the majority, are printed in regular typeface. The colour red is used for a rubrica, that is the subtitles which mark the psalter’s individual sections, such as the Invitatorium, feria, hymns, etc. This enables even those who have no command of Croatian to gain insight into the entire content of the psalter. Contrary to current opinion which claims the psalter to be the work of a Venetian school, and contrary to an isolated view that it was created at Zadar itself, the author deems that the psalter was created in the circle of Bologna, most likely around 1460 or soon after this date.